Distinct Transcriptional and Alternative Splicing Signatures of Decidual CD4+ T Cells in Early Human Pregnancy - Zeng, Weihong; Liu, Zhicui; Liu, Xinmei; Zhang, Siming; Khanniche, Asma; Zheng, Ying; Ma, Xiaoling; Yu, Tiantian; Tian, Fuju; Liu, Xiao-Rui; Fan, Jianxia; Lin, Yi (Frontiers in Immunology, 2017)
Decidual CD4+ T (dCD4 T) cells are crucial for the maternal-fetal immune tolerance required for a healthy pregnancy outcome. However, their molecular and functional characteristics are not well elucidated. In this study, we performed the first analysis of transcriptional and alternative splicing (AS) landscapes for paired decidual and peripheral blood CD4+ T (pCD4 T) cells in human early pregnancy using high throughput mRNA sequencing. Our data showed that dCD4 T cells are endowed with a unique transcriptional signature when compared to pCD4 T cells: dCD4 T cells upregulate 1695 genes enriched in immune system process whereas downregulate 1011 genes mainly related to mRNA catabolic process and the ribosome. Moreover, dCD4 T cells were observed to be at M phase, and show increased activation, proliferation and cytokine production, as well as display an effector-memory phenotype and a heterogenous nature containing Th1, Th17 and Treg cell subsets. However, dCD4 T cells undergo a comparable number of upregulated and downregulated AS events, both of which are enriched in the genes related to cellular metabolic process. And the changes at the AS event level do not reflect measurable differences at the gene expression level in dCD4 T cells. Collectively, our findings provide a comprehensive portrait of the unique transcriptional signature and AS profile of CD4+ T cells in human decidua and help us gain more understanding of the functional characteristic of these cells during early pregnancy.